DEVELOPING CULTURAL COMPETENCE IN STUDENTS THROUGH THE INTEGRATION OF UZBEK FOLK DANCE MOTIFS: A PEDAGOGICAL FRAMEWORK - Asror Allayarov (Modern American Journals, 2025)
In an increasingly globalized world, fostering cultural competence among students is essential for promoting intercultural understanding and personal growth. This article explores an innovative pedagogical methodology that leverages motifs from Uzbek folk dance art to enhance students' cultural awareness, empathy, and appreciation of traditional heritage. Drawing on the rich tapestry of Uzbek folklore, including regional dance styles such as Ferghana, Khorezm, and Bukhara, the proposed framework integrates experiential learning, interdisciplinary activities, and reflective practices. Through case studies and theoretical analysis, the study demonstrates how these motifs can be adapted into educational curricula to develop key competencies like cultural sensitivity and creative expression. The methodology emphasizes inclusivity, making it applicable across diverse educational settings. Findings suggest that such approaches not only preserve cultural legacies but also empower students to navigate multicultural environments effectively.
Keywords: Cultural competence, Uzbek folk dance, Folklore motifs, Pedagogical methodology, Student development